Quorum sensing systems and related virulence factors in Pseudomonas aeruginosa isolated from chicken meat and ground beef - Gökhan İnat (Nature Portfolio, 2021)
Abstract The objective of this study was to evaluate 50 [chicken meat (n = 45) and ground beef (n = 5)] Pseudomonas aeruginosa isolates to determine the expression of the lasI and rhl QS systems, related virulence factors, and the presence of N-3-oxo-dodecanoyl homoserine lactone (AHL: 3-O-C12-HSL). For the isolation and identification of P. aeruginosa, conventional culture and oprL gene-based molecular techniques were used. In relation to QS systems, eight genes consisting of four intact and four internal (lasI/R, rhlI/R) genes were analyzed with PCR assay. The two QS systems genes in P. aeruginosa isolates from ground beef (80.00%) and chicken meat (76.00%) were present at quite high levels. The 3-O-C12-HSL was detected in 14.00% of the isolates. Both biofilm formation and motility were detected in 98.00% of the isolates. Protease activity was determined in 54.00% of the isolates. Pyocyanin production was detected in 48.00% of the isolates. The las system scores strongly and positively correlated with the rhl system (p ˂ .01). PYA moderately and positively correlated with protease (p ˂ .05). In addition, there was statistically significance between lasI and protease activity (p < .10), and rhlI and twitching motility (p < .10). In conclusion, the high number of isolates having QS systems and related virulence factors are critical for public health. Pyocyanin, protease, and biofilm formation can cause spoilage and play essential role in food spoilage and food safety.